Older Adults Vs Middle-Aged Adults: Step Length (International Journal of Innovative Research in Computer Science & Technology, 2021)
The objective of the present study was to  evaluate step length of middle-aged adults and older adults.  Ten adults (14 middle age adults and 14 older adults) were  recruited from a local community. They were all physically  healthy and not injured in the last 6 months. One marker was  placed on each heel (right and left heels) and the position  data were collected during subsequent 5-minute walking on  a straight track (15m long). The results indicated that step  length of middle-age adults were larger than that of older  adults during their natural gait. The study concluded that  middle-age adults would likely to be involved in slips and  falls.
Keywords: Step Length; Middle age; Older; Falls